MURABAHAH FINANCING REPAYMENT OPTIMIZATION THROUGH 5C CREDIT ANALYSIS - Rapiyudin, Raply; Alifa, Nabiela Rizki (Finansha: Journal of Sharia Financial Management, 2024)
This study investigates the impact of the 5C credit analysis principles (Character, Capacity, Capital, Collateral, and Conditions of Economics) on the smoothness of murabahah financing payments at KSPPS BMT ItQan Soreang Unit either simultaneously or partially. Micro, Small, and Medium Enterprises (MSE) often face challenges due to a lack of business capital, despite financial products introduced by institutions like Savings and Loans Cooperatives and KSPPS BMT. Persisting issues in payment smoothness necessitate a comprehensive examination, particularly in credit analysis. This research employs a quantitative approach with logistic regression tests on a sample of 101 respondents using statistical techniques such as  regression analiysis, wald test, and omnibus test of model coefficients. This research highlights the importance of applying the 5C credit analysis principles to improve risk management, policy development, operational efficiency, and financial inclusion in murabahah financing at KSPPS BMT ItQan Soreang Unit. Findings from the Omnibus Test of Model Coefficients confirm that the 5C principles collectively impact payment smoothness. Moreover, the Wald test identifies Character, Capacity, and Conditions of Economics as significant contributors to the effectiveness of murabahah financing payments at KSPPS BMT ItQan Soreang Unit. This research highlights the importance of applying the 5C credit analysis principles to improve risk management, policy development, operational efficiency, and financial inclusion in murabahah financing at KSPPS BMT ItQan Soreang Unit.